Ionic conducting ceramic-carbonate dual phase hollow fibre membranes for high temperature carbon dioxide separation - Zuo, M.; Zhuang, S.; Tan, X.; Meng, B.; Yang, N.; Liu, Shaomin (Elsevier B.V, 2014)
In this work, the gas tight ceramic–carbonate dual phase hollow fibre membranes were developed in stages. To this end, oxygen ionic conducting ceramic of yttria stabilized zirconia (YSZ) hollow fibre was firstly prepared and structurally optimised for its application as the porous support to infiltrate the melting carbonate phase at high temperatures. The dual phase hollow fibre membranes were characterised by SEM, XRD, room-temperature gas leakage detection and CO2 permeation test at temperatures between 550 °C and 950 °C. The maximum CO2 flux measured reached 0.22 mL cm-2 min-1 at 950 °C.